Role of chlamydia antibody by using microimmunofluorescence in detection of tubal disease in infertile females. Issue 2 (June 2016) - Latif, Salama Abd Al; Fekry, Hesham; Altaf, Ahmed; Mohammed, Mona
Abstract : Objectives: The present study was conducted to assess the ability of the chlamydia antibody test (CAT) in the detection of tubal disease. Methods: Sixty women participated in the current study. They were investigated by using hysterosalpingography (HSG), followed by the CAT and laparoscopy. Results: The diagnostic accuracy of HSG was 70%, with sensitivity of 85%, specificity of 59%, positive predictive value of 61%, and negative predictive value of 83%. The CAT showed a diagnostic accuracy of 88%, sensitivity of 96%, specificity of 82%, positive predictive value of 81%, and negative predictive value of 97%. There was a substantial agreement between the results of CAT and HSG in the assessment of tubal disease with a κ value of 0.631. As regards the type of infertility, CAT was found to be more positive with secondary than primary infertility. Conclusion: The CAT is a good method for the detection of tubal patency in an outpatient setting.